Choice and democratic order : the French Socialist Party ; 1937 - 1950 - Graham, Bruce Desmond 1931- (Cambridge Univ. Press, 1994)
Choice and Democratic Order applies theories of group conflicts within political parties in a discussion of the internal politics of the French Socialist Party (SFIO) from the late 1930s to the 1940s. Having analysed the formal and informal structure of the party in 1937, Professor Graham gives a detailed account of the clash which took place between the leadership and two dissenting groups, the Gauche Revolutionnaire and the Bataille Socialiste, prior to the Royan Congress of June 1938. This conflict is compared with that which occurred in the post-war party during 1946, when Guy Mollet led a successful revolt against the party leaders and became General Secretary of the organization after the 38th National Congress. Mollet began with the intention of preserving the existing alliance with the Communists, but as the latter moved into opposition he accepted the necessity of the centre alliance, the so-called 'Third Force' in French politics. Choice and Democratic Order provides much important new information on a confused but compelling episode in modern French history, and will appeal to both historians and political scientists. Professor Graham emphasizes the continuities between the pre- and post-war periods, and his chosen approach enables the reader to observe major figures like Leon Blum and Guy Mollet working within the complex party structures of French socialism.